4CPS-002 Analysis and improvement of professionnal practices: prescription's evaluation of proton pump inhibitors in oral routes. (March 2019) - Heim, A; Pereira, L; Marchand, M; Bonnefous, M; Sénard, JM; Duhalde, V; Juillard Condat, B; Cestac, P
Abstract : Background: Proton pump inhibitors (PPI) continue to be one of the most prescribed drugs, mainly for elderly persons. According to available data, their prescriptions are non-conforming with guidelines in 25%–70% of cases. In the case of the therapeutic class that had an appropriate profile of adverse effects in the short term, their prescriptions are trivialised. Outside of proved adverse effects such as fracture risk, allergic events and digestive disorders, a literature review reports a relationship with new adverse effects such as risk of renal failure and dementia in the long term that should be confirmed by future studies. Purpose: In the context of the mandatory part of contract for quality improvements and efficiency of care between health-care institutions, Regional Health Agency and Health Insurance, a regional audit has been proposed and performed. The purpose of this study is to evaluate the good use of PPI and then improve hospital professional practices. Material and methods: In accordance with the proposed regional methodology, 50 patients' records including 25 aged over 65 years old have been drawn by lot among all clinical poles, with prescriptions of PPI by oral routes in February and April 2018. The regional audit schedule validated by the Observatory of Drugs, Medical Devices and Therapeutic Innovation and Pharmacovigilance Regional Centre permitted the data to be used and calculated the non-conformity percentage. Criteria of concern were: liver failure, history of peptic ulcer, bleeding or bowel perforation, taking nonsteroidal anti-inflammatories, anticoagulant, platelet aggregation, indication, prescribed medication, dose and length of treatment. Criteria conforming were established regarding characteristics, products summary and formal guidelines from the French National Authority for Health and National Agency for Medicines. Results: In total, only 22% of the prescriptions were conforming. Among the 39 prescriptions that were non-conforming, , 77% was as a result of indications, 13% resulting from the products and 10% as a result of dose or period non-conforming. Conclusion: This audit proposed fields of improvement to promote the good use of PPI: a feedback to prescribers and information on their good use will be taken. Pooling regional results will enable a synthesis that will be returned to the participating hospitals. References and/or acknowledgements: https://ejhp.bmj.com/content/23/Suppl_1/A243.1 No conflict of interest.